Nuclear dynamics: Formation of bodies and trafficking in plant nuclei - Muñoz-Díaz, Eduardo; Sáez-Vásquez, Julio (Frontiers in Plant Science, 2022)
The existence of the nucleus distinguishes prokaryotes and eukaryotes. Apart from containing most of the genetic material, the nucleus possesses several nuclear bodies composed of protein and RNA molecules. The nucleus is separated from the cytoplasm by a double membrane, regulating the trafficking of molecules in- and outwards. Here, we investigate the composition and function of the different plant nuclear bodies and molecular clues involved in nuclear trafficking. The behavior of the nucleolus, Cajal bodies, dicing bodies, nuclear speckles, cyclophilin-containing bodies, photobodies and DNA damage foci is analyzed in response to different abiotic stresses. Furthermore, we research the literature to collect the different protein localization signals that rule nucleocytoplasmic trafficking. These signals include the different types of nuclear localization signals (NLSs) for nuclear import, and the nuclear export signals (NESs) for nuclear export. In contrast to these unidirectional-movement signals, the existence of nucleocytoplasmic shuttling signals (NSSs) allows bidirectional movement through the nuclear envelope. Likewise, nucleolar signals are also described, which mainly include the nucleolar localization signals (NoLSs) controlling nucleolar import. In contrast, few examples of nucleolar export signals, called nucleoplasmic localization signals (NpLSs) or nucleolar export signals (NoESs), have been reported. The existence of consensus sequences for these localization signals led to the generation of prediction tools, allowing the detection of these signals from an amino acid sequence. Additionally, the effect of high temperatures as well as different post-translational modifications in nuclear and nucleolar import and export is discussed.